Islam Tionghoa di Tengah Politik Multikulturalisme di Kota Makassar - Karim, Syahrir (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2021)
This paper examines the position of ethnic Chinese in local politics, especially in Makassar City. Analyzing the relationships and Muslim-majority communities in shaping their political positioning in Makassar City. This paper aims to explain the position of Chinese and Chinese Islam in every moment of democratic contestation as well as the strategic implications of the political position of ethnic Chinese in the midst of the majority in Makassar City. This research was conducted using qualitative methods. The result of this study indicate that Chinese Muslims in Makassar City have multiple identities on the one hand they prioritize their Islamic status and on the other hand they continue to prioritize their Chinese identity. Cultural factors, religion, the process of assimilation in society and changes in the national and local political climate are all influencing factors in seeing Chinese identity.